(untitled) (Indian Journal of Public Health Research & Development, 2021)
WHO 2019 report on drinking water says that In 2017, 71% of the global population (5.3 billion people) used a safely managed drinking-water service – that is, one located on premises, available when needed, and free from contamination.. Most countries, the proportions of piped and other-improved water supplies are faecally contaminated sources due to lack of basic sanitary protection against contamination. Contaminated water is an important contributor to water borne disease including hepatitis A,cholera, typhoid, and poliomyelitis.1 For people with enough water supply can treat their water at home after testing water quality to ensure microbiological quality. Treating water at the household level or other point of use also reduces the risk of waterborne disease arising from recontamination during collection, transport, and use in the home. This article mainly focuses on need for water quality monitoring,water quality, types of water quality testing the importance of water quality monitoring and reviews related to water quality testing.